(untitled) (Journal of Dhaka Medical College, 2010)
A middle aged lady presented with recurrent jaundice with normal SGPT, serum alkaline phosphatase, serum albumin and prothrombin time. Haemolysis was excluded by normal haemoglobin, peripheral blood film and reticulocyte count and finally she was diagnosed to have Gilbert’s syndrome. Key words: Gilbert’s Syndrome; Hyperbilirubinaemia. DOI: 10.3329/jdmc.v19i1.6257 J Dhaka Med Coll. 2010; 19(1) : 67-68.